White sponge nevus as a hereditary disease: A brief narrative review - Mahdani, Fatma Yasmin; Puspasari, Karlina; Manuaba, Ida Bagus Pramana Putra; Putri, Salsabila Fitriana; Ayunnisa, Naqiya; Ernawati, Diah Savitri; Hendarti, Hening Tuti (Indonesian Journal of Dental Medicine, 2025)
Background: White sponge nevus (WSN) is an autosomal dominant hereditary genetic disorder characterized by thickened keratin in the oral mucosa that appears folded, wavy, spongy, thick, and rough. WSN do not have the potential to become malignant, but an accurate diagnosis is still needed to prevent unnecessary treatment and reduce potential remissions and exacerbations due to infection. Purpose: to provide a detailed description of white sponge nevus as a hereditary disease by means of narrative review. Review: A literature search using ScienceDirect and PubMed yielded results between 2012 and 2024. The keywords of the search strategy were “hereditary disease” and “white sponge nevus” or “Cannon’s disease” or “white folded gingivostomatitis” or “leukokeratosis.”. White sponge nevus (WSN) was first discovered by Hyde in 1909 and usually occurs in children and people under 20 years old. The main etiology of WSN is an autosomal dominant hereditary genetic disorder; KRT4 and KRT13 are specific keratin encoders that cause WSN, and there are predisposing factors such as bacterial infection, smoking, and alcohol consumption. Conclusion: In determining the diagnosis of WSN, it is necessary to carry out blood tests, subjective examinations, objective examinations, and supporting examinations in the form of exfoliative cytology and biopsies. As well as the need for comprehensive treatment, even though the prognosis of this disorder is good.